OPERATIONAL MANAGEMENT OF FISHING PORT NATIONALSIBOLGA REGENCY OF MIDDLE TAPANULI NORTH SUMATERA PROVINCE - Arifah, Nur; Zain, Jonny; ', Syaifuddin (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2016)
This research was conducted in 10-26 February 2016 in the ocean fishing port Sibolga. This research aims to examine operational management of Fishing Port National the most important about elements and funcitions application operational management. The study was conducted using a survey method and the analysis data that is done are and SWOT analysis .The study was conducted by taking the primary and secondary of the data for 10 days. Based on the result of research then result using SWOT analysis so the Fishing Port National Sibolga including quadrant I which is a very profitable situation and have a opportunities then take use strategist for operational management development is progressive strategist.Keyword : Operational management, SWOT analysis, Sibolga fishing port.